The concept of «Dutch disease» in economy (International relations and international law Journal, 2016)
The article deals the theoretical aspects of the concepts «Dutch disease» in economy and the reasons of feature and a consequence of «Dutch disease» (a phenomenon of economic development of the countries having considerable resources of raw materials) in Republic of Kazakhstan. In this paper is the question of existence of «Dutch disease» in Russia and Kazakhstan is of special interest. However many researchers have only partially confirmed existence of some symptoms of «Dutch disease» at the export countries of natural resources – or did not find such confirmations at all. After all obstacles for development of economy are created not by existence of resources in itself, and the related calls on which it is possible and it is necessary to look for adequate answers. The author analyzes a hypothesis of «Dutch disease» and compare it with error of the program Excel.
Keywords: natural resource; Dutch disease; phenomenon; hypothesis; symptom; raw